Analisis Yuridis Penyelesaian Sengketa Hak Kekayaan Intelektual di Indonesia - Putra Ardianto (Federalisme: Jurnal Kajian Hukum dan Ilmu Komunikasi, 2026)
A creative work is a work produced by a creator, while a creator can be defined as an individual who, individually or collectively, produces a creation based on expertise, imagination, skills, proficiency, and various other elements that are expressed in a tangible form. In its application, Copyright is vulnerable to disputes due to limited regulations and the lack of certainty regarding the subject matter involved. In this regard, Intellectual Property Rights disputes in Indonesia can be resolved through two mechanisms: litigation, which involves the role of the courts, and non-litigation, namely dispute resolution conducted outside the court through arbitration and other institutions. The laws governing the settlement of Intellectual Property Rights disputes can be found in Law No. 31 of 2000 concerning Industrial Designs and Law No. 32 of 2000 concerning Layout Designs of Integrated Circuits. Furthermore, Law No. 13 of 2016 concerning Patents, Law No. 20 of 2016 concerning Trademarks, and Law No. 28 of 2014 concerning Copyright explicitly stipulate that disputes relating to intellectual property fall under the jurisdiction of the Commercial Court.